دليل مصادر تاريخ الأندلس و أدبه في مكتبات جامعة البصرة - مطرود، عارف عبدالكريم (جامعة البصرة - كلية الآداب, 2010)
تعد الكتب والمكتبات في كل أنحاء العالم واجهة حضارية وعلمية مهمة جدا، فهي تعكس تطور البلد أو تخلفه، وبها يعلو التراث وتنشط الحضارة، ويسمو التسابق العلمي المستمر. هدف البحث تقديم خدمة بسيطة لطالب العلم، لمتابعة مصادره في مكتبات الجامعة بيسر وسهولة، دون معاناة. \ آلية العمل \ كنت أسجل من رفوف المكتبات مباشرة: اسم الكتاب واسم مؤلفه واسم المحقق، ثم مكان الطبع وفي أي سنة طبع بدءا بمصادر تاريخ الأندلس ثم بمصادر أدبه، مبتدأ بالمكتبة المركزية وهكذا...استغرق هذا العمل أياما عدة، جمعت فيها كل المصادر والمجلات والرسائل والأطاريح المتعلقة بالمجال نفسه. \ الصعوبات والمقترحات \ واجهتني صعوبات كثيرة لإنجاز البحث منها: أنني لم أجد في أكثر المكتبات سجلات لكافة الكتب التي تحتويها، ووجدت بعض المكتبات مهملة إذ يعلوها التراب وغير مرتبة، وفي بعض الأحيان أجدها ممزقة ولقد ثبت ذلك في البحث. \ وللأمانة وجدت تعاونا ملحوظا لبعض المكتبات من قبل موظفيها، ومن أجل رفع مستوى مكتبات جامعتنا قدمت مقترحات أجدها مهمة وضرورية... \ وبعد ذلك عملت إحصائية بأعداد الكتب المتوفرة في مكتبات جامعة البصرة الإنسانية. The aim of the research: \ Books and libraries, all over the world, are considered to be civil and scintifical facet for they reflect the progress or the failure of the country. They are the means by which the heribage and the civilization rise and the scintifical race may go on. The aim of the search is to present a simple service to the scholars to follow their resources easily. \ The mechanism of the work: \ I had recording directly: The name of the book, the name of its author and its researcher and then the printing place and the year of printing starting from the books of history to the literary books of Andlaus. I started form the central library and so on …. This lasted many days. I collected all resources, magazines, letters and theses that belong to the same field. \ Difficulties and Suggestions: \ I faced many problems to fulfill this research among them is: I didn't find records for all books in most of these libraries. Instead I found some libraries neglected with books covered by dust and sometimes I found these books torn and I mentioned that in the research. \ Honestly some of these libraries made cooperation. I made suggestions to raise our libraries and put them in good level. \ After all I made data of numbers of the books which are available in the literary libraries of University of Basra .
Keywords: العراق -- تاريخ الأندلس -- المصادر التاريخية -- مصادر تاريخ الأندلس -- المكتبات الجامعية -- الببليوجرافيات